The Effectiveness of Pregnancy Exercise Education Using Squatting Pose and Pelvic Rocking to Improve Maternal Knowledge and Prevent Perineal Rupture - Melissa Princess Rahmadhena; Mega Suci Ambarwati; Anisa Marsely; Cindy Meiliani Rinandha; Ethics of Styo Rahayu; Karina Karina; Maghfira Izani Masliah; Siti Lela; Susi Lailah (Postgraduate, University of Mataram, 2025)
One of the efforts to reduce the incidence of perineal rupture during labor is through specific techniques that can enhance the elasticity and flexibility of the perineal tissue and strengthen the pelvic floor muscles. Two commonly recommended techniques are the Squatting Pose and Pelvic Rocking. These techniques can help reposition the fetus, facilitate the delivery process, and minimize the risk of perineal injury by relaxing the pelvic muscles and strengthening the muscles involved in childbirth. This study aims to investigate the effect of Squatting Pose and Pelvic Rocking on the incidence of perineal rupture in laboring women. This research employed a quasi-experimental design with an intervention and control approach. The independent variable in this study was pregnancy exercise, specifically the squatting pose, while the dependent variable was the incidence of perineal rupture. A total of 160 respondents were included in this study, consisting of pregnant mothers aged 37-39 weeks, divided into two groups: 80 respondents in the intervention group (who performed Squatting Pose and Pelvic Rocking) and 80 respondents in the control group (who did not perform these exercises), selected through purposive sampling. A Mann-Whitney test was conducted, and the results showed no significant difference in the incidence of perineal rupture between the intervention and control groups (p-value 0.079). However, when examining the degree of perineal rupture, the control group had a higher degree of rupture compared to the intervention group. This suggests that although Squatting Pose and Pelvic Rocking may not significantly reduce the incidence of perineal rupture, they may help reduce the severity of the tear, which is beneficial for postpartum recovery. It is recommended that these exercises be incorporated into childbirth preparation programs in clinics and homes, as they may aid in the recovery process after delivery.